Desempenho produtivo e reprodutivo de cordeiras recebendo suplementação concentrada em comedouro privativo - Ortiz, Jessé Siqueira; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Silva, Marina Gabriela Berchiol da [UNESP]; Hadlich, Janaina Conte [UNESP]; Cavassano, Francielli Aparecida; Garcia, Cledson Augusto (Pontificia Universidade Catolica do Parana - PUCPR, 2013)
Ewes with high fertility and prolificacy rates with ability to reduce lamb mortality are sought as matrix replacements in sheep herds. The objective of this study was to evaluate the effect of different levels of concentrate supplementation containing 18% CP and 3.15 Mcal/kg/DM during creep feeding of lambs on their weight and performance at different ages, the onset of puberty and reproductive performance. Thirty-six Suffolk lambswere used, divided into three levels of concentrate intake (1, 2.5 and 4% of body weight). The animals were fed from birth to weaning. Feed was supplied once a day and daily leftovers were recorded. The lambs were identified, weighed at birth, 30 days and 60 days of age, when they were weaned. There was no significant difference in body weight and average daily weight gain at 30 and 60 days of age. The intake levels did not affect the parameters measured. The daily supplementation with 4% concentrate provided better reproductive performance in the first and second year of mating, but did not increase the number of lambs per birth.

Para reposição de matrizes ovinas buscam-se fêmeas com elevadas taxas de fertilidade e prolificidade dotadas de habilidade materna visando reduzir a mortalidade dos cordeiros. Com o objetivo de avaliar o efeito de níveis de suplementação concentrada contendo 18% de PB e 3,15 Mcal EM/kg/MS para cordeiras em comedouro privativo sobre peso e desempenho em distintas idades, início da puberdade e desempenho reprodutivo, foram utilizadas 36 cordeiras Suffolk, divididas em três níveis de ingestão de concentrado 1; 2,5 e 4% do peso vivo, alimentadas do nascimento ao desmame, sendo fornecido uma vez ao dia com o registro das sobras diárias. As cordeiras foram identificadas, pesadas ao nascimento e a cada 30 dias, sendo desmamadas aos 60 dias. Não houve diferença significativa para peso e ganho de peso médio diário aos 30 e 60 dias de idade. Os níveis de ingestão não influenciaram os parâmetros analisados. A suplementação diária de 4% do peso vivo para as cordeiras até o desmame, promoveu melhor desempenho reprodutivo no primeiro e segundo ano de cobertura, porém não aumentou o número de cordeiros por parto.
Productive and reproductive performance of lambs receiving concentrate supplementation in private feeder
Keywords: Lambs; Creep feeding; Suffolk; Puberty; Borregas; Creep feeding; Suffolk; Puberdade